Penerapan Terapi Endorphin Massage Untuk Adaptasi Tingkat Nyeri Persalinan Pada Ibu Primigravida Di Ruang Anggrek (Vk) Rsud. Dr T.C Hillers Maumere. - Fransiska K Kolin; Regina Ona Adesta (Lembaga Pengembangan Kinerja Dosen, 2024)
The problem that most often arises in women giving birth normally is labor pain, this pain occurs due to uterine contractions, dilatation and effacement of the cervix, decreased presentation of the vagina and perineum. If this pain is allowed to persist, the mother feels uncomfortable, anxious, scared and worried, which will help the condition of the mother and fetus. One way to reduce pain is by doing endorphin massage therapy. The aim of this case study is to determine the adaptation of labor pain levels in primigravida mothers after endorphin massage therapy. The method used in this case study was designed using a case study approach with a nursing care process approach. The subjects in this case study were 2 patients, obtained from inclusion and exclusion criteria, data collection using the Numerical Rating Scale (NRS). The results of the case study show that the average pain level of the two patients after being given endorphin massage therapy intervention for ± 2 hours changed from severe pain to moderate pain and the patients looked more comfortable, calm and relaxed. The conclusion of this case study shows that there were changes that occurred after the endorphin massage therapy intervention was given to the two patients and the pain scale decreased so that the two patients were able to adapt to the pain they felt.